Applying camp management methods to urban displacement in Afghanistan - Hirsch-Holland, A (Refugee Studies Centre, University of Oxford, 2020)
Applying key elements of the traditional camp management approach can enhance communication, community participation and coordination in out-of-camp urban contexts.